ELEGIBILITY AND INELIGIBILITY: ASSESSMENT OF ELEGIBILITYASSUMPTIONS AND INELEGIBILITY HYPOTHESES ACCORDIND TOCONSTITUCIONAL LAW AND ELECTORAL LAW (REMUNOM, 2025)
This article aims to examine the requirements for eligibility and the grounds for ineligibilityestablished by the 1988 Federal Constitution and related legislation, from the perspective ofConstitutional Law and Electoral Law. The analysis is justified by the need to deepen theunderstanding of these requirements, providing greater clarity to the electorate and serving as abasis for future research in the field. The central issue consists of identifying the causes of ineligibilityestablished in the 1988 Constitution. Although the constitutional text sets forth specific conditions forcandidacy, legal doctrine presents divergences regarding the interpretation of certain provisions,which underscores the importance of this study. In this context, the research objectives were definedas follows: the general objective is to analyze the conditions of eligibility provided for in the 1988Constitution; and the specific objectives are to compare doctrinal divergences concerning ineligibility,to conceptualize the legislation related to Constitutional Law, and to highlight the main requirementsof eligibility and ineligibility. The investigation adopts a qualitative approach, based on a bibliographicreview of an exploratory nature, which enabled the systematization of information and theformulation of relevant considerations. Finally, it was found that the right to vote constitutes one ofthe people’s greatest assets, representing the transfer of trust to the elected candidate, from whomgovernance guided by justice, ethics, and dignity is expected.